Strontium- and cobalt-substituted bioactive glasses seeded with human umbilical cord perivascular cells to promote bone regeneration via enhanced osteogenic and angiogenic activities. (August 2017) - Kargozar, Saeid; Lotfibakhshaiesh, Nasrin; Ai, Jafar; Mozafari, Masoud; Brouki Milan, Peiman; Hamzehlou, Sepideh; Barati, Mahmood; Baino, Francesco; Hill, Robert G.; Joghataei, Mohammad Taghi
Graphical abstract: Highlights: Melt-derived Sr- and Co-substituted bioactive glasses (BGs) were synthesized. BG granules significantly enhanced osteogenic activity of human osteosarcoma cells. BG granules significantly promoted angiogenic activity of human endothelial cells. HUCPVCs-seeded BG constructs promoted bone healing in a rabbit experimental model. Abstract: Designing and developing new biomaterials to accelerate bone healing are currently under progress. In this study, we attempted to promote osteogenesis using strontium- and cobalt-substituted bioactive glasses (BGs) seeded with human umbilical cord perivascular cells (HUCPVCs) in a critical size defect in the distal femur of rabbit animal model. The BG particles were successfully synthesized in the form of granules using the melt-derived route. After being isolated, HUCPVCs were expanded and then characterized to use during in vitro and in vivo procedures. The in vitro effects of the synthesized glasses on the isolated HUCPVCs as well as on cell lines SaOS-2 (selected for screening the osteogenetic potential) and HUVEC (selected for screening the angiogenic potential) were assessed by analyzing cytotoxicity, cell attachment, bone-like nodule formation, and real time PCR. The results of in vitro tests indicated cytocompatibility of the synthesized BG particles. For in vivo study, the HUCPVCs-seeded BGs were implanted into the animal's body. Radiographic imaging, histology and immunohistology staining were performed on the harvested specimens at 4 and 12 weeks post-surgery. The in vivo evaluation of the samples showed that all the cell/glass constructs accelerated bone healing process in comparison with blank controls. The best in vitro and in vivo results were associated to the BGs containing both strontium and cobalt ions. This group of bioactive glasses is able to promote both osteogenesis and angiogenesis and can therefore be highly suitable for the development of advanced functional bone substitutes. Statement of Significance: Bone regeneration is considered as an unmet clinical need. The most recent researches focused on incorporation of strontium (Sr 2+ ) and cobalt (Co 2+ ) ions into bioactive glasses structure. Strontium is an alkaline earth metal which is currently used in the treatment of osteoporosis. Also, cobalt is considered as another promising element in the bone regeneration field that may induce hypoxia-mediated angiogenesis. In this study, the osteogenic potential of the strontium- and cobalt-substituted bioactive glasses in granule form seeded with human umbilical cord perivascular cells (HUCPVCs) was evaluated in vitro and in vivo . Indeed, the main goal of this study was to improve the osteogenenic and angiogenic properties of bioactive glasses through the incorporation of strontium and cobalt ions in the glass composition. Although some researches have been conducted on this subject, the influence of the simultaneous use of strontium and cobalt ions on the improvement of bone healing in vivo has been not yet well understood and, therefore, deserves further investigation.